2012
DOI: 10.1155/2012/173614
|View full text |Cite
|
Sign up to set email alerts
|

In VitroSchistosomicidal Activity of Some Brazilian Cerrado Species and Their Isolated Compounds

Abstract: Miconia langsdorffii Cogn. (Melastomataceae), Roupala montana Aubl. (Proteaceae), Struthanthus syringifolius (Mart.) (Loranthaceae), and Schefflera vinosa (Cham. & Schltdl.) Frodin (Araliaceae) are plant species from the Brazilian Cerrado whose schistosomicidal potential has not yet been described. The crude extracts, fractions, the triterpenes betulin, oleanolic acid, ursolic acid and the flavonoids quercetin 3-O-β-D-rhamnoside, quercetin 3-O-β-D-glucoside, quercetin 3-O-β-D-glucopyranosyl-(1-2)-α-L-rhamnopyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…The terpenes with antischistosomal activity are: rotundifolone [66], (+)-limonene epoxide [56], and carvacryl acetate, a derivative of carvacrol (monoterpenes) [39]; artemisinin and its derivatives [30,31], nerolidol [59], and budlein-A and its derivatives [38] (sesquiterpenes); phytol [60] (diterpene), betulin [37] and its triphenylphosphonium derivatives [69], balsaminol F, karavilagenin C [36] (triterpenes) (Figure 1). Importantly, among the group of terpenes, in vitro and in vivo antischistosomal properties have been described only for artemisinin and its derivatives, phytol and triphenylphosphonium derivatives, whereas it was reported in vitro schitosomicidal activity for other terpenes (Table 1).…”
Section: Terpenesmentioning
confidence: 99%
See 3 more Smart Citations
“…The terpenes with antischistosomal activity are: rotundifolone [66], (+)-limonene epoxide [56], and carvacryl acetate, a derivative of carvacrol (monoterpenes) [39]; artemisinin and its derivatives [30,31], nerolidol [59], and budlein-A and its derivatives [38] (sesquiterpenes); phytol [60] (diterpene), betulin [37] and its triphenylphosphonium derivatives [69], balsaminol F, karavilagenin C [36] (triterpenes) (Figure 1). Importantly, among the group of terpenes, in vitro and in vivo antischistosomal properties have been described only for artemisinin and its derivatives, phytol and triphenylphosphonium derivatives, whereas it was reported in vitro schitosomicidal activity for other terpenes (Table 1).…”
Section: Terpenesmentioning
confidence: 99%
“…A recent study has showed that betulin isolated from Schefflera vinosa (Araliaceae), a plant from the Brazilian Savannah, was effective in vitro against S. mansoni adult worms at a concentration of 100-200 μM [37]. More recently, Spivak et al [69] have synthesized triphenylphosphonium derivatives of betulin and betulinic acid and results showed in vitro antischistosomal of activity against newly transformed schistosomula and adult worms of S. mansoni at low micromolar concentrations (<10 μM and <2 μM, respectively).…”
Section: Triterpenesmentioning
confidence: 99%
See 2 more Smart Citations
“…As part of our advancing investigation on the schistosomicidal activity of Brazilian species from "Cerrado" and "Pantanal" [10][11][12], the present work reports on the in vitro schistosomicidal activity of the ethanolic extract and three isolated 5-methoxy-flavones from V. divergens leaves.…”
Section: Introductionmentioning
confidence: 99%